STRUCTURE DESIGN OF PARKING BUILDING SUNTER PARK VIEW APARTMENT WITH THE EQUIVALENT STATIC ANALYSIS METHOD - Wuritno, Bambang (Jurnal Teknik Sipil dan Perencanaan, 2013)
Parking building (Tower C), Project Sunter Park View Apartment is a public facility that serves as a parking garage. This building consists of 4 floors including the roof plate with a typical floor plan for each level. Floor to floor elevation is 3 meters height, so the total height of the building reach 9 meters height (less than 40 meters height). Review Design Parking building structure (Tower C) Project Title: "Structure Design Of Parking Building Sunter Park View Apartment With The Equivalent Static Analysis Methodâ€ , wherein the influence of earthquakes on structures analyzed by Equivalent Static method based on the Standard Provisions Design for Earthquake Resistance of Building Structures (SNI 03-1726-2002). Structural components of buildings designed by Special Moment Frame System Bearers (SRPMK) based on Procedure for Calculation of Concrete Structure for Buildings (SNI 03-2847-2002).